The right of states to regulate in international investment law the search for balance between public interest and fair and equitable treatment - Levashova, Yulia (International arbitration law library ;, 2019)
"The Right of States to Regulate in International Investment Law addresses the balance between the host state⁰́₉s right to regulate and the investor⁰́₉s right to obtain a fair and equitable treatment (FET) standard under international investment law. Due to the recent ongoing expansion of public interest issues worldwide, the state⁰́₉s right to regulate has been recaptured as a prominent concept in international investment law. The FET⁰́₉s standard provision in the text of an international investment agreement (IIA) has become a detailed clause clarifying the specific obligations of a state towards an investor under the FET standard. However, striking the right balance in these new treaty formulations has proved to be challenging. This book greatly clarifies the field by offering in-depth analysis of the application of the state⁰́₉s right to regulate in relation to FET standard provisions in IIAs and to decisions by arbitral tribunals in FET cases"--Publisher's website